2018
DOI: 10.1016/j.bmc.2017.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Novel fluconazole derivatives with promising antifungal activity

Abstract: The fungistatic nature and toxicity concern associated with the azole drugs currently on the market have resulted in an increased demand for new azole antifungal agents for which these problematic characteristics do not exist. The extensive use of azoles has resulted in fungal strains capable of resisting the action of these drugs. Herein, we report the synthesis and antifungal activity of novel fluconazole (FLC) analogues with alkyl-, aryl-, cycloalkyl-, and dialkyl-amino substituents. We evaluated their anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…Exact structure: bactericidal activity against Staphylococcus aureus and Escherichia coli (Niu et al 2018; Savage Paul 2017), pesticidal activity (Park et al 2018), anti-inflammatory activity (Wrasidlo and Natala 2018), antifungal activity against Candida and Aspergillus species by inhibiting ergosterol synthesis (Chandrika, et al 2018; Garneau-Tsodikova et al 2018), used as a component in traditional Chinese medicine for the treatment of Coronary heart disease complicated with depression (Zhang et al 2018a, b)…”
Section: Resultsmentioning
confidence: 99%
“…Exact structure: bactericidal activity against Staphylococcus aureus and Escherichia coli (Niu et al 2018; Savage Paul 2017), pesticidal activity (Park et al 2018), anti-inflammatory activity (Wrasidlo and Natala 2018), antifungal activity against Candida and Aspergillus species by inhibiting ergosterol synthesis (Chandrika, et al 2018; Garneau-Tsodikova et al 2018), used as a component in traditional Chinese medicine for the treatment of Coronary heart disease complicated with depression (Zhang et al 2018a, b)…”
Section: Resultsmentioning
confidence: 99%
“…Azole derivatives show great potential activities against Candida infections. Chandrika et al developed 12 novel azole derivatives that showed significant antifungal activities against different types of Candida spp., but none of them was C. auris [22]. Similarly, Shrestha et al, successfully developed some novel alkylated-azoles that showed great activities against 13 clinically fungal isolates, but C. auris was not one of them [23].…”
Section: Discussionmentioning
confidence: 99%
“…Fungal Features— Cryptococcus neoformans , a basidiomycete fungus involved in meningitis, can lead to a poor outcome in patients who are immunocompromised [ 160 ]. The treatments are limited to anti-fungal agents such as amphotericin B (which binds to sterol in fungal cell membranes, leading to pore formation and ultimately fungal death [ 161 ]) and fluconazole (which disrupts the fungal membrane and ergosterol synthesis) [ 162 ]). However, these drugs elicit side effects including kidney damage [ 160 ] and thus, other agents are needed to improve treatment responses.…”
Section: Fungal Infectionsmentioning
confidence: 99%